PRAKTIK ETIKA ISLAM DAN PASAR: BUKTI DARI INSTITUSI KEUANGAN ISLAM - Nabila Prahaski; Chuzaimah Batubara (CV. ADIBA AISHA AMIRA, 2023)
The market from Islamic ethical practices will pay attention, among other things, to the process of obtaining the right supply from the right suppliers, performing Sharia-compliant processes efficiently and innovatively, with the ultimate goal of providing halal, environmentally friendly, ethical, and socially responsible products and services to customers. The main objective of this research is to examine the market dimensions of 37 Islamic financial institutions in Indonesia for the year 2012. Content analysis of annual reports and sustainability reports was used to examine their current market practices. Semi- structured interviews were also conducted to validate the findings and clarify emerging issues. The marketplace involves stakeholder engagement activities followed by marketing activities. The disclosure of Islamic principles and values in market-related policies has received insufficient attention. This indicates that Islamic financial institutions do not strategically incorporate Islamic principles and values into their market dimension-related policies. To some extent, the interview results support the content analysis findings. The interviews conducted revealed that the motivation for stakeholder engagement in Islamic institutions is to address issues of zakat distribution